Green Infrastructure for Socio-Ecologically Resilient Cities: The Case of Amman City Center, Jordan - Alshafei, Islam Abdel-Latif M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Densely populated areas pose challenges for the local governments to tackle with the social and environmental problems of urbanization such as degraded natural environment, social and environmental injustice, reduced feeling of well-being, increased air temperatures, and high flooding risks, leaving urban communities vulnerable to stressors. These global challenges place a pressing encounter for urban environments demanding more resilient systems that can deal with the stresses of urbanization. Moving on from this perspective, the research focuses on the socio-ecological theory of resilience, in an attempt to understand how this discipline evolved over the years to host the human ecosystem approach to study the interactions between social and ecological systems, and highlight approaches to reinstate nature into urban areas through the integration of urban Green Infrastructure (GI). The literature review indicates that there is limited research on the application of this approach in the field of urban planning and highlights the fact that GI embraces a potential for strengthening resilience and assisting disaster risk reduction (DRR). As such, the research focuses on understanding how GI can be implemented into the human ecosystem spatial networks of challenging inner-city urban contexts to reach socio-ecological resiliency, versus developing tactical solutions during emergency situations. Accordingly, a theoretical framework is proposed that approaches the reciprocal relationships between spatial patterns and sociocultural processes through the use of an integrated systems approach where the natural and cultural landscape can be spatially and functionally integrated to enable the creation of more socio-ecologically resilient cities through a GI oriented approach. The research utilizes a mixed methodology where both quantitative and qualitative data are collected and analyzed. Questionnaire surveys are employed to measure the pro-environmental behavior of local communities in the city center of Amman. The methodology uses quantitative tools based on graph/space syntax theories. It is argued that these two methods withhold powerful diagnostic tools for the improvement of socio-ecological resilience in dense urban areas as in the case of Amman through visualizing and assessing human ecosystem spatial patterns to develop tactical solutions in emergency situations. The findings of the study address the possibilities for the enhancement of the patchiness of the ecological system by re-establishing a socially driven landscape connectivity where GI can be developed and sustained. To this end, the study offers benefits for the development of socio-ecological resiliency and DRR within the context of the case and similar cases by suggesting specific context-sensitive aspects within its framework that can be generalized for planning, implementing, and managing urban GI, building resiliency capacities, and reducing vulnerabilities in urban communities.

ÖZ: Yüksek nüfusa sahip yerleşimler, hızlı kentleşmenin yol açtığı bozulmuş doğal alanlar, sosyal ve çevresel adeletsizlik, insan sağlığının olumsuz etkilenmesi, hava sıcaklığının artması, sel ve taşkın riskinin yükselmesi gibi sosyal ve çevresel sorunlara neden olarak, kent topluluklarını streslere karşı daha duyarlı hale getirmekte ve yerel yönetimlerin acil durumlar karşısında mücadele edebilme kabiliyetlerini olumsuz etkilemektedir. Halbuki dünyamızda daha kaliteli kentsel çevrelerin yaratılması, kentleşmenin etkileri ve stresleriyle başa çıkabilen daha esnek sistemlerin oluşturulması ile mümkündür. Bu çerçeveden hareketle, kentlerde sosyal ve ekolojik sistemler arasındaki etkileşimleri insan ekosistemi yaklaşımı üzerinden inceleyen bu çalışma, bu kavramın zaman içinde farklı disiplinlerde nasıl dönüştüğüne bakarak, sosyo-ekolojik esneklik kuramına odaklanmakta ve doğanın kendini yenileyebilmesi için Yeşil Altyapı’nın (YA), kent alan larına nasıl dahil edilebileceğini araştırmaktadır. Literatür taraması, bu konunun kentsel planlama alanında sınırlı bir araştırmaya konu olduğunu kanıtlamakta, ve YA’nın kentsel toplulukların direncinin güçlendirilmesinde ve afet risklerinin azaltılmasında önemli bir role sahip olduğu göstermektedir. Bu çerçevede araştırma, Ürdün'deki Amman şehir merkezi örneğinde, YA’nın, kentlerde sosyo-ekolojik esnekliği sağlamak ve afet durumlarında acil tedbirler üretebilmek için karmaşık kent sistemlerinde nasıl uygulandığı konusuna odaklanmaktadır. Bu hedefle, YA planlamasında mekansal ve işlevsel olarak kente bakmak yanında insan hareketinin de dikkate alınarak entegre bir sistem yaklaşımının geliştirilmesinin önemini vurgulayan çalışma, mekansal örüntüler ve sosyokültürel süreçler arasındaki ilişkileri incelemektedir. Araştırma, hem nicel hem de nitel verilerin toplandığı ve analiz edildiği karma bir metodolojik yaklaşımı benimsemektedir. Çevreye Duyarlı Davranışları (ÇDD) ölçen bir anket yöntemine başvuran araştırma, aynı zamanda grafik/mekan sentaks teorilerine dayalı nicel araçlardan da faydalanmaktadır. Bu iki yöntem entegre olarak kullanıldığında, Amman ve benzeri alan çalışmalarında, bağlama duyarlı bir yaklaşımla kent sistemlerinde sosyo-ekolojik esnekliğin geliştirilmesi ve afet durumlarında acil tedbirler üretilmesi amacı ile kullanılabilecektir. Çalışmanın bulguları, YA’nın peyzaj sistemleri arasındaki ekolojik bağların sosyal ilişkiler ağı ile birlikte değerlendirildiği zaman sürdürülebilir bir yapıya sahip olabileceğini ortaya koymuştur. Kentlerin sosyal ve ekolojik sistemlerindeki kırılganlıkları tolere edebilmesi için kentlerin daha esnek bir yapıya sahip olmalarının önemine vurgu yapan çalışma, YA’nın kentteki sosyal ilişkilerin de incelenerek planlanlanabilmesi, uygulanabilmesi ve yönetilmesi için metodolojik bir çerçeve sunmakta ve benzeri dinamiklere sahip bağlamlarda sosyo-ekolojik esnekliği sağlamak ve doğal afet risklerini azaltmak için öneriler sunmaktadır.
Doctor of Philosophy in Architecture. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2022. Supervisor: Asst. Prof. Dr. Pınar Uluçay Righelato.
Keywords: Architecture Department; City and town--Green Infrastructure--Urban Planning--Amman (Jordan); Green Design--Social aspects; Space (Architecture)--Social aspects; Sociology, Urban; Green technology; Environmental technology--Architecture; Infrastructure (Economics)--Environmental aspects; City planning--Environmental aspects; Socio-ecological Resiliency, Green Infrastructure “GI”, Disaster Risk Reduction “DRR”, Pro-environmental behavior, Space Syntax Theory, Graph Theory.